Hot Alignment Solution Using Spreadsheet Application - Kasim, Mohd Shahir; S.A Faizal; Raja Abdullah, Raja Izamshah; Che Zainal Abidin, Nik Mohd Farid (2007)
Over the past twenty years, the level of awarness concerning the importance of accurate and precise shadr alignment has increase dramatically. Therefore shaft alignment seems to have taken more more important role when installing and maintaining machinery. Proper alignment is critical to the life of the machine. Coupling wear or failure, bearing failure, bent rotors or crankshaft, plus bearing housing damage are all common results of poor alignment. When machinery is operating, the moving parts cause friction that in turn creates heat buid-up causing the macinery to expand. this expansion in the machinery is called thermal growth. by neglecting the thermal growth factor, an alignment process changes from simple job into an all dayy affair frequency with unsatifactory result, despite conscientious effort and a considerable in manpower and down time. There a lot of tools on the market to make the mathematics simple, however, a graphic picture shows the whole problem at glance and makes the solution apparent. This paper discussed on the development of shaft alignment procedures using spreadsheet namely as ALIGN. This approach can reduce calculation process and minimize error during shaft alignment process.